Enteric Parasitic in canines (Canis familiaris) in the urban area of Coroico, Nor Yungas department of La Paz Bolivia - Llanos Mariana; Condori Marcelina; Ibáñez Teddy; Loza-Murguia Manuel (Journal of the Selva Andina Research Society, 2010)
A wide variety species of intestinal protozoa and helminthes are pathogen for the domestic animals. Between April and November 2009, a study was done with the purpose of determining the enteric parasitic infection in dogs (Cannis familiaris), 96 dogs (58 males and 38 females) with owner of 10 species, one hybrid, eight age groups in two seasons of the urban area of the Coroico town, Nor Yungas, department of La Paz, Bolivia. The coproparasitology diagnostic was made by direct examination, with the Willis-Molloy flotation simple technique with a solution oversaturated of sodium chloride. It was detected one or more species of helminthes and protozoa, was used the chi-square and descriptive method for the statistical analysis. The results were: from the 96 sampled dogs, in 87% is present at less one type of parasitic shape, were identify: Ancylostoma spp, Toxocara canis, Strogyloides spp, Giardia spp, Isospora canis, Trichuris vulpis, Ancylostoma spp/Uncinaria spp and Dipylidium caninum. The evaluation by season show a (p ≤ 0,05) for the Giardia spp. In a humidity season, but not for a dry season, the rest of parasites can be found in both seasons. By sex in a humidity season T.canis in females 43% and 22% in males, in dry season by sex was found T.vulpis in female with a high frequency (p ≤ 0,05), the rest of parasites do not show statistic differences in both seasons. By age in dry season T. canis and Stronyiloides sp. prevails 1-24 months and 49-72 months respectively, in a humidity season T. canis prevails in the same age (p ≤ 0,05). By race in dry season Ancylostoma spp Uncinaria spp prevails in the race Pekingese, in humidity season Strongyloides sp prevails in the Cocker race. Prevail in both seasons A. canis y T. canis. In relation to the mono-parasitism and multi-parasitism, was viewed, in both seasons the dogs multi-parasitism are more than the mono-parasitism.